Neurosurgical Complications Following Tooth Extraction: A Systematic Review and Individual Patient Meta-Analysis - Shafa, Shahram; Entezar-Almahdi, Elahe; Pourdavood, Amir Hossein; Vosooghinezhad, Behzad; Zarenezhad, Mohammad; Jodaei, Armin; Ghafari, Narges; Taheri, Lohrasb; Zarei, Tayyebeh; Bagheri, Nastaran; Ghaedi, Mojtaba; Kazemi Nia, Marjan; et al. (Galen Medical Journal, 2024)
Background: We aimed to review the characteristics of patients with neurosurgical complications after tooth extraction. Materials and Methods: This systematic review followed PRISMA guidelines and searched PubMed/MEDLINE, Embase, Web of Science, and Scopus databases for studies investigating neurosurgical complications post-tooth extraction. Relevant keywords for dental extraction, adverse events or complications, and neurosurgery were searched using Boolean operators. Extracted data was synthesized using proper statistical tests. Results: Among 42 studies, 47 cases (34 males, 13 females) were included. The complications were distributed as follows: 25 brain abscesses, 11 meningitis cases, 8 cerebrovascular accidents, 2 cases with both meningitis and stroke, and 1 pituitary macroadenoma. Four deaths occurred in cerebrovascular accident cases. A significant association was found between preexisting diseases and death (odds ratio = 2.15, 95% CI: 1.08-4.29, p-value = 0.03). Three mucormycosis and two mycobacterium tuberculosis cases were reported. The most common symptoms were headache (55.32%), fever (38.3%), and laterality symptoms (25.53%). Neck pain/neck rigidity was more prevalent in females (30.77% vs. 8.82%, P = 0.042), as were nausea and vomiting (30.77% vs. 8.82%, P = 0.028). Overall, 31.91% of cases had no underlying diseases. The mean time from tooth extraction to emergency room visit was 19.73 days (SD = 31.01 days), ranging from 2 to 180 days. Fourteen cases (29.79%) involved the upper jaw, 6 (12.77%) the lower jaw, and 2 (4.26%) both jaws. Conclusion: The study introduces a novel approach by systematically reviewing and analyzing individual patient data to identify specific risk factors and symptoms associated with neurosurgical complications following tooth extraction. Healthcare providers can use the identified symptoms, such as headache and fever, as key indicators for prompt evaluation and management of patients presenting after tooth extraction, especially in male patients with pre-existing conditions who are undergoing upper jaw teeth extraction.